Edema hepático - Adorni, Orestes E. (1941)
The author does a “mise au point” upon the theme, reminding Mac Swinney and De Giovanni’s first works; these separated his pathogeny from mechanical theory which predominated then; he continues exposing De Damany’s principal work to establish after the clinical tableau with all its varieties, and to follow later with the revision of every invoked theory to explain these types of oede- mes, and he finishes with the exposition of toxic factors of the Imidazoles group which hydropigenic roll has been experimentally established. He arrives at the conclusion that these oedemes don’t obey to an only causal but to a group of them —mechanical, endocrinal, nervous, tumoral and chemical— intimately connected among them.